A evolução das receitas provenientes dos royalties do petróleo e seus impactos na arrecadação dos tributos de competência municipal (2002 – 2007): o caso do município de Cabo Frio/RJ - Villas Bôas, Bruno Fonseca (2008)
There are about ten years the municipal districts bordering with Campos' Basin is registering continuous and vigorous increase of the incomes originating from the incident government participations on the exploration and production of petroleum and natural gas in function of the Law Federal n° 9.478/98 that, among another measured, it enlarged the basic brackets of royalties of 5% for up to 10% of the value of the production as well as it instituted the payment of special participations on the profit obtained in fields of great production or profitability. In that work we looked for to analyze the behavior, in the Municipal City hall of Cabo Frio, of the incomes in epigraph during the period understood among the financial exercises from 2002 to 2007, verifying the effects produced in the tributes collected by that Executive, as well as evaluating the administrations, through the analysis of the collected data, in the sense of to determine in which there was larger effectiveness in the outturn of them. The study in screen intends to be a source of information for futures managers, aiding them in the transport of fiscal and administrative politics that they seek to increase the collection.